Christianity and American Democracy - Heclo, Hugh (The Alexis de Tocqueville lectures on American politics, 2007)
Christianity, not religion in general, has been important for American democracy. With this bold thesis, Heclo offers a panoramic view of how Christianity and democracy have shaped each other over the years, and how their relationship is changing in the present day. Responding to his challenging argument, Mary Jo Bane, Michael Kazin, and Alan Wolfe criticize, qualify, and amend it. The result is a lively debate about a momentous tension in American public life.